Design of a flexible surface/interlayer for packaging. Issue 11 (28th February 2022) - Zhan, Fei; Gao, Weina; Zhao, Feng; Qin, Peng; Sun, Xinlong; Sun, Chenkun; Tang, Shousheng; Wang, Lei
Abstract : A flexible multi-level topography and hollow interlayer not only reduce the maximum stress and maximum strain on the surface of the structure (a–e), but also enhance the thermal isolation performance (f). Abstract : Impact resistance and thermal insulation are important factors to be considered in the fields of encapsulation and drug transportation. In this study, a classic circular sleeve structure is designed by integrating the multi-level surface topography of the sleeve and a hollow sandwich in the wall, which effectively improves the energy absorption efficiency and thermal insulation effect. With the increase of the levels of surface structure, the stiffness of the whole structure and the stress on the topmost structure decreases, which is conducive to protecting the structure. In addition, the thermal conduction efficiency can be limited and the heat preservation ability would be improved as the reduction of the contacting area of packages with internal objects is attributed to such specific topography. Moreover, the synergistic effect of the hollow sandwich further enhances the advantages of mechanics and heat insulation. Based on the findings of this study, this novel design has potential applications in fields such as thermal insulation, packaging, and pharmaceuticals.